Simplicity in vision : a multidisciplinary account of perceptual organization - Helm, Peter A. van der (Cambridge University Press, 2014)
Perceptual organization is the neuro-cognitive process that enables us to perceive scenes as structured wholes consisting of objects arranged in space. Simplicity in Vision explores the intriguing idea that these perceived wholes are given by the simplest organizations of the scenes.